Relationship between Soil Fertility and Growth Performance of Planted Shorea macrophylla at Reforestation Sites of Sampadi Forest Reserve, Sarawak, Malaysia - Mugunthan, Perumal (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Information on the soil properties and growth performance under artificial forest initiated after reforestation activity is important in order to understand the ecological information as a useful tool and guideline for further improvement of future reforestation activities, especially in the humid tropics of Sarawak. In this study, a preliminary survey and assessment was conducted in order to evaluate the growth performance and survival rate of planted Shorea macrophylla at various age stands that were implemented by Forest Department, Sarawak along with several agencies of Japan at Sampadi Forest Reserve, Sarawak, Malaysia. The present study was carried out to elucidate the current status of the soil morphological and physicochemical properties of the planted forests under reforestation in comparison to an adjacent secondary forest. Besides, this study also aims to examine soil fertility status and site quality of the planted forests with a special reference to two indices; Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF) as well as to test the applicability of these indices which are commonly used for estimating soil fertility and productivity of regenerating secondary forests in humid tropical regions. Shorea macrophylla planted under line planting technique was selected in this study. Study plots with the size of 75 m x 50 m per age stand (subdivided into 6 subplots; 25 m x 25 m in each subplots) were established in the reforestation areas (planted with Shorea macrophylla in the year 1996; SM96, 1997; SM97, 1998; SM98 and 1999; SM99). Diameter at breast height (DBH), total height, percentage of survival and light intensity were measured. Soil samples were collected at the depth of 0-10 cm (surface soils) and 30-40 cm (subsurface soils) from several random points at plots in reforested areas (SM96, SM97, SM98 and SM99) and secondary forest (SF) for soil physicochemical properties determination. Soil profile description was conducted in the center of each study site to obtain basic information on the soil morphological properties of the studied sites. Standard soil analysis for both physical and chemical properties was used to analyze the soil samples. The findings indicated a positive growth pattern in terms of growth performance and survival which clarified the efficacy of line planting technique used in this study. Nonetheless, growth performance in terms of survivability, mean annual increment of height (MAIH) and diameter (MAID) in SM96 revealed the highest and showed most favorable growth as compared to SM97, SM98 and SM99. High percentage of survival of Shorea macrophylla were depicted in this study with 89% of survival in SM96, followed by 80%, 82% and 57% in SM97, SM98 and SM99, respectively. Notwithstanding, the results from soil morphological properties has proven that the existence of Bako soil series which derived from sandy residual parent material as a dominant unit in associate with Saratok series which leads to the identification of Grey-White Podzolic soil group in the study area. The results indicated that the soils both in rehabilitated forest and secondary forest were strongly acidic in nature with pH (H2O) values less than (pH 5.50) at surface and subsurface soils. The soils consisted of sandy clay loam to sandy clay in texture with low fertility level and poor in nutrient status associated with high level of Al saturation. The negative charges derived from the organic matter and clay minerals plays a vital role in retaining soil nutrients and probably influence the soil nutrient status. Principal Component Analysis (PCA) revealed the soil properties into three most significant components which explained vii 76.3% of the total variation. The first component score (PC1) was related to phosphorus content, soil acidity and soil texture. PC2 infers soil organic matter constituent and cation retention capacity, while PC3 related to available nutrient of the soils. The linear regression analysis indicated that there were positive correlations between PC1 score and the proposed SFI at surface soils (r = 0.789, P < 0.01). Nevertheless, the SFI was also highly correlated with diameter at breast height (DBH), height and survival of the planted Shorea macrophylla. Thus, these significant correlations between SFI and growth performance suggested that SFI to be applied as an index for estimating soil fertility and site quality for rehabilitation forest in the tropics under line planting technique. However, no correlation was found with the SEF. Thus, it can be concluded that line planting technique has proven to be a suitable approach and Shorea macrophylla as one of the appropriate indigenous choice of species for future reforestation and rehabilitation activities as it offers potential to improve site productivity and also could be a target for ecosystem rehabilitation where the trees can eventually dominate the forest structure and encourage the recovery of biodiversity in the future. Notwithstanding, it is recommended that proper silvicultural technique is crucial to manage the existing pioneer tree species towards the success of this reforestation programme.